2015
DOI: 10.1021/es5049754
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Inactivation of Viruses in Open-Water Unit Process Treatment Wetlands: Modeling Endogenous and Exogenous Inactivation Rates

Abstract: Sunlight inactivation is an important mode of disinfection for viruses in surface waters. In constructed wetlands, for example, open-water cells can be used to promote sunlight disinfection and remove pathogenic viruses from wastewater. To aid in the design of these systems, we developed predictive models of virus attenuation that account for endogenous and exogenous sunlight-mediated inactivation mechanisms. Inactivation rate models were developed for two viruses, MS2 and poliovirus type 3; laboratory- and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 72 publications
6
80
0
Order By: Relevance
“…Figure 9b shows free water surface flow wetlands are expected to achieve a wide range of removal of bacteria and viruses that can range from less than 1 log 10 reduction to up to 2 or 3 log 10 reduction. This supports the conclusions of others (e.g., Nguyen et al, 2015;Silverman et al, 2015) that sunlight inactivation is very important for virus and bacteria reductions and this mechanism may be limited in a free water surface flow constructed wetland that contains emergent plants because of shading of the water by the vegetation. The observations in Figure 9a and 9b are also supported by who showed that horizontal subsurface flow constructed wetlands typically have a better capacity to remove pathogens than a planted free water surface flow constructed wetlands.…”
Section: Summary Of Data On Pathogen Removal In Constructed Wetland Ssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 9b shows free water surface flow wetlands are expected to achieve a wide range of removal of bacteria and viruses that can range from less than 1 log 10 reduction to up to 2 or 3 log 10 reduction. This supports the conclusions of others (e.g., Nguyen et al, 2015;Silverman et al, 2015) that sunlight inactivation is very important for virus and bacteria reductions and this mechanism may be limited in a free water surface flow constructed wetland that contains emergent plants because of shading of the water by the vegetation. The observations in Figure 9a and 9b are also supported by who showed that horizontal subsurface flow constructed wetlands typically have a better capacity to remove pathogens than a planted free water surface flow constructed wetlands.…”
Section: Summary Of Data On Pathogen Removal In Constructed Wetland Ssupporting
confidence: 90%
“…Sunlight is also rapidly attenuated within the first few centimeters of a pond-like system that contains wastewater or natural organic matter (Davies-Colley et al, 2005b). The issue of sunlight exposure in a planted system is especially important because there is a direct relationship between the amount of sunlight that reaches a pathogen and the inactivation rate Silverman et al 2015). The inactivation of viruses by sunlight and the influence that different parts of the solar spectrum have on different viral species is discussed by Silverman et al (2013).…”
Section: Sunlight and Water Claritymentioning
confidence: 99%
“…In contrast, the inactivation of human adenovirus was less accurate, and was underestimated two-fold. Silverman et al (2015) pursued a similar approach. This group also considered total solar inactivation as the sum of endogenous and exogenous processes.…”
Section: Introductionmentioning
confidence: 99%
“…As a subclass, shallow open-water unit process wetlands were developed as a specialized component of larger engineered wetland systems that receive municipal wastewater effluent and effluent-dominated surface waters. These units were initially designed to enhance the removal of recalcitrant trace organic contaminants such as pharmaceuticals and personal care products (24-26) but were found to have ancillary benefits for nitrate (2) and pathogen attenuation (27,28) through an interplay of photolytic and biological processes that rivaled or even surpassed their vegetated cousins. The open-water unit process wetland is lined with a geotextile fabric in order to prevent the growth of macrophytes that would shade the water column and contains a benthic photosynthetic biomat that when mature can be up to 10 cm thick.…”
mentioning
confidence: 99%